Teknologi Live Streaming Agency" menjadi "Kapabilitas Inti dan Keunggulan Kompetitif Berkelanjutan Berbasis VRIO pada Live Streaming Agency PT Check Out Time (COT) - Brian Kalti Pranata; Edi Hamdi; Dimas Angga Negoro; Muhammad Dhafi Iskandar (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
This study aims to analyze PT COT's internal factors by identifying its strengths and weaknesses, as well as evaluating its resources and capabilities using a SWOT analysis and the VRIO framework. The research method used was a descriptive qualitative case study approach, with data collected through interviews, observations, and documentation studies. The results indicate that PT COT possesses key strengths in the form of high-quality studios and production equipment, data analytics technology (BICOT), a competent production team, a relevant KOL network, pricing flexibility, content creativity, and strategic partnerships with major brands. However, its weaknesses include limited access to marketplace platforms and low brand awareness. Therefore, the recommended strategy is to strengthen digital marketing to increase brand visibility, expand business partnerships, and continue investing in technology and human resource development. This study confirms that PT COT has a strong internal foundation to compete in the e-commerce live streaming industry, but further optimization is needed to build a sustainable competitive advantage.